ANOVA to Compare Three Methods to Track COVID-19 in Nine Countries: ANOVA en la comparación de tres métodos para rastrear COVID-19 en nueve países - Juárez Lucero, Jorge Jaime; Sánchez-Sánchez, Anabel; Díaz-Hernández, Raquel; Guevara-Villa, María del Rayo; Altamirano-Robles, Leopoldo (Revista Mexicana de Ingenieria Biomedica, 2021)
A new coronavirus denominated first 2019-nCoV and later SARS-CoV-2 was found in Wuhan, China in December of 2019. This paper compares three mathematical methods: nonlinear regression, SIR, and SEIR epidemic models, to track the covid-19 disease in nine countries affected by the SARS-CoV-2 virus, to help epidemiologists to know the disease trajectory, considering initial data in the pandemic, mainly 100 days from the beginning. To evaluate the results obtained with the three methods one-way ANOVA is applied. The average of predicted infected cases with SARS-CoV-2, obtained with the mentioned methods was: for United States of America 1,098,508, followed by Spain with 226,721, Italy with 202,953, France with 183,897 United Kingdom with 182,190, Germany with 159,407, Canada with 58,696, Mexico with 50,366 and Argentina with 4,860 in average. The one-way ANOVA does not show a significant difference among the results of the projected infected cases by SARS-CoV-2, using nonlinear regression, SIR, and SEIR epidemic methods. The above could mean that initially any method can be used to model the pandemic course.